1990
DOI: 10.1007/bf01344276
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids indicate differences in diet of the hydrothermal vent crabBythograea thermydron (Brachyura)

Abstract: Carotenoid pigments were used as markers to investigate the sources of energy to two deep-sea hydrothermal vent communities. Specimens of the hydrothermal-vent brachyuran crab Bythograea thermydron were collected at 2 500 m depth from the Rose Garden vent site in the Gal/tpagos Rift Valley in February, November and December 1979, and 2 600 m depth on the East Pacific Rise at 21°N in May 1982. Four carotenoids (astaxanthin, canthaxanthin, echinenone and beta-carotene) have been identified as the pigments respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…–Galapagos Rift, Rose Garden vent site; 2500 m; February, November and December 1979; 215 crabs collected from traps (DeBevoise, Childress & Withers, 1990).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…–Galapagos Rift, Rose Garden vent site; 2500 m; February, November and December 1979; 215 crabs collected from traps (DeBevoise, Childress & Withers, 1990).…”
Section: Resultsmentioning
confidence: 99%
“…–EPR, collapse pit site; 20°50′N, 109°00′W; 2600 m; May 1982; from traps; 19 specimens (DeBevoise et al. , 1990).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Nègre-Sadargues et al [38], carotenoid pigments are obtained from bacteria, fungi, or plants. DeBevoise et al [39] suggested that the carotenoids found in the crab eggs of Bythograea thermydron are produced in situ by chemoautotrophic bacteria present and are not derived from phytodetritus as one may expect.…”
Section: Discussionmentioning
confidence: 99%